Effectiveness of a peer education gender and health project for men in Timor‐Leste. (31st May 2020) - Smith, Helen; Botfield, Jessica R.; Soares, Marce; Cheng, Yan; McGeechan, Kevin
Abstract: Issue Addressed: In response to high rates of gender‐based violence and poor sexual and reproductive health indicators in Timor‐Leste, a 'Men's Health Project' was implemented in two rural communities in 2013. A peer education model was utilised to engage men in issues regarding health, relationships and well‐being. Methods: Community‐based baseline and endline surveys were undertaken to evaluate the project in the two communities. Results: In 2013, 401 men and boys completed a baseline survey, and 400 completed an endline survey in 2016. Significant differences were found in a number of areas, with more men in the endline survey aware of the negative impacts of alcohol, safe pregnancy practices, family planning and sexually transmitted infections. Many men reported making the major decisions in their family in both surveys. Conclusions: The peer education approach engaged men in health awareness and contributed to increasing knowledge of sexual and reproductive health and other health issues. However, while education and positive attitudes are an important foundation for change, other enabling mechanisms including vital infrastructure, services and health personnel must be in place to facilitate change and increase access to information and healthcare. Findings highlight the importance of engaging both women and men in processes of challenging behaviours and structures that reinforce gender inequalities. So What?: Peer education appears to be an effective model for engaging community members in gender and health issues in Timor‐Leste. The Men's Health Project enabled men to participate in health awareness and issues regarding health, relationships and well‐being.